Cytotoxic Activity of CuO NPs Prepared by PLAL Against Liver Cancer (Hep-G2) Cell Line and HdFn Cell Lines - Huda Hussein Abbas; Sabah N. Mazhir (Iraqi Journal of Physics, 2023)
A simple physical technique was used in this study to create stable and cost-effective copper oxide (CuO) nanoparticles from pure copper metal using the pulsed laser ablation technique. The synthesis of crystalline CuO nanoparticles was confirmed by various analytical techniques such as particle concentration measurement using atomic absorption spectrometry (AAS), field emission scanning electron microscopy (FE-SEM), the energy dispersive X-ray (EDX), and X-ray diffraction (XRD) to determine the crystal size and identify of the crystal structure of the prepared particles. The main characteristic diffraction peaks of the three samples were consistent. The corresponding 2θ is also consistent, and the cytotoxicity of the nanoparticles was also investigated. After 24 hours of exposure, the percentage of cytotoxicity was calculated. The maximum toxicity of Hep-G2 was 37.81% at the maximum concentration of (500) µg mL-1 after 24 hours of exposure. Also, the maximum toxicity of the normal cell line was 27.85% at a maximum concentration of (500) µg mL-1.